2012
DOI: 10.1111/tid.12025
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of programmed death receptor‐1 signaling restores expression of mostly proinflammatory cytokines in anergic cytomegalovirus‐specific T cells

Abstract: Taken together, this pilot study provides evidence that a high PD-1 expression on CMV-specific T cells actively impairs proliferation and "cytokinome" responses in an antigen-specific manner. Importantly, blockade of PD-L restores CMV-specific T-cell proliferation and expression of a panel of different proinflammatory and/or type 1 cytokines, suggesting a common but as yet unknown regulatory principle. We conclude that PD-1 exhaustion is reversible and potentially amenable to therapeutic ex vivo and possibly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…A high percentage of PD1+, CD38+ circulating T cells has also been found in other chronic diseases such as graft-versus-host disease [45] and chronic herpes virus infections [35,36]. In the latter it was linked to a reduced life span of the affected persons [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high percentage of PD1+, CD38+ circulating T cells has also been found in other chronic diseases such as graft-versus-host disease [45] and chronic herpes virus infections [35,36]. In the latter it was linked to a reduced life span of the affected persons [46].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a monoallergy did not have these CD4+ , CD25 dim , CD38+, and PD-1+ T cells [8]. Initially it was speculated that the continued CD38+ and PD-1+ expression within the CD4+, CD25 dim cell fraction might be due to an ongoing infection by endogenous herpes viruses, as the PD1+/CD38+ phenotype was also observed in chronic herpes virus infections [35,36]. However, a viral analysis of the patients failed to document an ongoing herpes virus (cytomegalovirus and HHV6) infection.…”
Section: Patho-mechanism Of Mdhmentioning
confidence: 99%
“…14,15 The combinatorial use of celecoxib with PD-1 mAb completely suppresses the upregulation of the inflammatory genes, including IL-1b and IL-6, both of which play critical roles in promoting tumor progression. 48,49 This observation provides the additional justification for the combined utilization of these two drugs for treating tumors.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 We next examined the expression of typical inflammatory molecules COX2, IL-1b, IL-6, iNOS and TNF-a, and of the anti-inflammatory molecule IL-10, and VEGF. While anti-PD-1 mAb delivery alone did not change the mRNA levels of iNOS, TNF-a, IL-10 and VEGF (data not shown), and the mRNA levels of COX2, IL-1b, IL-6, were increased ( Fig.…”
Section: Dual Delivery Of Celecoxib and Anti-pd-1 Mab Inhibits Angiogmentioning
confidence: 99%
“…However, studies have shown that blocking different coinhibitory molecules might exert a synergistic effect on immunotherapy for sepsis. [567273] With respect to the appropriate timing for anti-PD-1/PD-L1 antibody administration, Brahmamdam et al . [51] showed that when the anti-PD-1 antibody was given to mice 24 h after the induction of sepsis, the survival rate increased.…”
Section: Research On the Blockade Of The Programmed Cell Death-1/progmentioning
confidence: 99%